2003
DOI: 10.1095/biolreprod.102.007997
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Uterine Epithelial Apoptosis Is Associated with Expression of Mitochondrial Voltage-Dependent Anion Channels, Release of Cytochrome C from Mitochondria, and the Ratio of Bax to Bcl-2 or Bcl-X1

Abstract: The release of cytochrome c from mitochondria, which is regulated by Bcl-2 family members and is considered to take place through voltage-dependent anion channels (VDACs) on the outer membranes of mitochondria, results in activation of effector caspases, such as caspase-3, which induce apoptosis. We studied the involvement of the mitochondrial apoptosis pathway in uterine epithelial apoptosis. Estradiol-17beta pellets were implanted into ovariectomized mice and removed 4 days later (Day 0). The apoptotic index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 35 publications
2
27
0
1
Order By: Relevance
“…Recent studies indicated that VDAC plays an important role in drug-induced apoptosis [11,17]. It is known that arsenic trioxide could induce the upregulation of VDAC in apoptotic human myeloma cells and increased expression of VDAC is correlated with mouse uterine epithelial apoptosis [9,39]. Taken together, our results suggested that PoVDAC might be mediated fish antiviral immune response through induction of apoptosis.…”
Section: Discussionsupporting
confidence: 60%
“…Recent studies indicated that VDAC plays an important role in drug-induced apoptosis [11,17]. It is known that arsenic trioxide could induce the upregulation of VDAC in apoptotic human myeloma cells and increased expression of VDAC is correlated with mouse uterine epithelial apoptosis [9,39]. Taken together, our results suggested that PoVDAC might be mediated fish antiviral immune response through induction of apoptosis.…”
Section: Discussionsupporting
confidence: 60%
“…Depletion of these steroid hormones induces apoptosis of epithelial cells in these organs [1][2][3][4][5][6][7][8][9]. Although this phenomenon is well recognized, the mechanism of the signal transduction in initiation of apoptosis has not been fully elucidated [4,6,[8][9][10].…”
mentioning
confidence: 99%
“…Given that anti-and pro-apoptotic members interact with each other to suppress the activity of their partners (Bras et al, 2005;Oltvai et al, 1993;Willis and Adams, 2005), the ratios of protein or mRNA abundance between them are considered to be important factors in control of apoptosis (Cui and Kim, 2005;Hua et al, 2006;Kutlu et al, 2003;Köhler et al, 2002;Lynch et al, 2010;Mei et al, 2007;Takagi-Morishita et al, 2003;Viola-Rhenals et al, 2007;Xu et al, 2007). Actually, several studies had demonstrated that enhancement of the mRNA ratios of Bax, Bak and Bad to Bcl-xL were associated with the efficient induction of cellular apoptosis (Cui and Kim, 2005;Hua et al, 2006;Kutlu et al, 2003;Köhler et al, 2002;Takagi-Morishita et al, 2003;Xu et al, 2007). Similarly in the present study, EPO stimulation resulted in decreases in the mRNA ratios of Bax, Bak, and Bad to Bcl-xL, and concomitant reduction in apoptosis of late-stage erythroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Cell death is then induced through the activation of a cascade between caspase-9 and caspase-3 (Elmore, 2007). The balance of protein or mRNA abundance between the Bcl-2 family members is believed to regulate apoptosis and presumably determine the cell fate (Cui and Kim, 2005;Hua et al, 2006;Kutlu et al, 2003;Köhler et al, 2002;Lynch et al, 2010;Mei et al, 2007;Takagi-Morishita et al, 2003;Viola-Rhenals et al, 2007;Xu et al, 2007). In particular, it is known that Bcl-xL plays an important role as an antiapoptotic factor in erythropoiesis (Dolznig et al, 2002;Gregoli and Bondurant, 1997;Testa, 2004).…”
Section: Introductionmentioning
confidence: 99%